Role of protein kinase A signaling pathway in cyclosporine nephrotoxicity - Franca, F. D.; Ferreira, A. F.; Lara, R. C.; Rossoni, J. V.; Costa, D. C.; Moraes, K. C. M. [UNESP]; Gomes, D. A.; Tagliati, C. A.; Chaves, M. M. (Informa Healthcare, 2014)
Cyclosporine is an important immunosuppressive agent; however, nephrotoxicity is one of the main adverse effects. The purpose of this study was to evaluate the effect of inhibiting the protein kinase A (PKA) signaling pathway in nephrotoxicity caused by cyclosporine from the assessment of cell viability, pro-inflammatory cytokines, and nitric oxide (NO) production in LLC-PK1 and MDCK cell lines. Cyclosporine proved to be cytotoxic for both cell lines, as assessed by the mitochondrial enzyme activity assay (MTT), caused DNA fragmentation, determined by flow cytometry using the propidium iodide dye, and activated the PKA pathway (western blot assay). In MDCK cells, the inhibition of the PKA signaling pathway (H89 inhibitor) caused a significant reduction in DNA fragmentation. In both cell lines, the production of IL-6 proved to be a dependent PKA pathway, while TNF-alpha was not influenced by the inhibition of the PKA pathway. The NO production was increased when cells were pre-incubated with H89 followed by cyclosporine, and this production was dependent on the PKA pathway in LLC-PK1 and MDCK cells lines. Therefore, considering the present study's results, it can be concluded that the inhibition of PKA signaling pathway can aid in reducing the degree of nephrotoxicity caused by cyclosporine.
Keywords: Cyclosporine; IL-6; nephrotoxicity; NO; PKA; TNF-alpha